Antiphospholipid Syndrome Presenting as Mesenteric Vein Thrombosis and Gangrenous Small Bowel - WASR, Wan Ali; MS, Mohd Shahrir; H, Hussein (IIUM Medical Journal Malaysia, 2011)
A 35-year-old Jordanian gentleman presented with worsening right iliac fossa pain of three-day durations with vomiting, loose stool and intermittent fever. He later underwent laparoscopic surgery, which was subsequently converted to open laparotomy. Intraoperatively, there was thickened bowel with multiple mesenteric lymph nodes, and also thrombosis of the small bowel vein supplying the affected bowel lesion, the diagnosis which was later confirmed with the histopathological report. Resection with end-to-end anastomosis was done during the surgery. Within one-week post laparotomy, he developed another progressive abdominal pain and distension, vomiting and no bowel opening. He was sent for another exploratory laparotomy. Intraoperatively, there was a gangrenous small bowel segment measuring 130 cm, with an intact large bowel and previous anastomotic site. Resection of 150 cm of the small bowel was subsequently done.